DEVELOPMENT OF AN SCT-MODEL-BASED CHEMICAL BONDING E MAGAZINE TO ENHANCE STUDENTS' CRITICAL THINKING SKILLS AND KNOWLEDGE LEARNING OUTCOMES - Musfiroh, Yashinta Dwi; Saadi, Parham; Syahmani; Yogo Dwi Prasetyo (Universitas Negeri Surabaya, 2025)
Critical thinking skills and knowledge learning outcomes are very important for students in today's chemistry learning. However, the results of the PISA test, preliminary studies, and previous research indicate that both aspects still need to be improved. This study uses an R & D approach utilizing the ADDIE model to create a chemical bond e-magazine based on the SCT model that is valid, practical, and effective in enhancing critical thinking skills and knowledge learning outcomes. This study involved five expert validators and 66 grade XI students of SMA Negeri 8 Banjarmasin. The data were gathered through questionnaires, observation sheets, and tests, and then analyzed descriptively. The findings revealed that (1) the e-magazine produced demonstrated a high level of validity (90%) in terms of content, presentation, language, and media, (2) practical with an average score of 88%, and (3) effective with an N-Gain of 0.71 (critical thinking) and 0.75 (knowledge) categorized as high, with an average achievement score of 83%.